Learning path tracking system - Khalid, Khalina (2006)
Learning Path Tracking System (LPTS) is a system that will be used to produce student’s learning paths based on their result in every semester. The Learning Path Diagram is used to guide students clearly on subjects that have to be taken in every semester in order to complete their Masters program. LPTS consists of several modules that can be used as a mechanism to manage overall M.Sc. programme conducted by Advanced IT Institute (AITI). It varies from managing student and lecturer profiles up to managing subject registration and results. Reports generated not only useful for management but for all LPTS users. The absolute aim is to improve on student’s performance, as the Learning Path Diagram was developed to accelerate student’s progress so that they can complete their Masters program thoughtfully, systematically and quickly. Hopefully the LPTS will be successfully implemented and can be fully utilize not only by AITI but also UTM intentionally.